Integrating natriuretic peptides and diastolic dysfunction to predict adverse events in high-risk asymptomatic subjects - Gori, Mauro; Lam, Carolyn Sp; D'Elia, Emila; Iorio, Anna M; Calabrese, Alice; Canova, Paolo; Cioffi, Giovanni; De Maria, Renata; Ghirardi, Arianna; Iacovoni, Attilio; Grosu, Aurelia; Fontana, Alessandra; et al. (European journal of preventive cardiology, 2021)
Natriuretic peptides and diastolic dysfunction have prognostic value in asymptomatic subjects at risk for heart failure. Their integration might further refine the risk stratification process in this setting. Aim of this paper was to explore the possibility to predict heart failure and death combining diastolic dysfunction and natriuretic peptides in an asymptomatic population at risk for heart failure. Among 4047 subjects aged ≥55/≤80 years followed by 10 general practitioners in Italy, the DAVID-Berg study prospectively enrolled 623 asymptomatic outpatients at increased risk for heart failure. Baseline evaluation included electrocardiogram, echocardiogram, and natriuretic peptides collection. Based on diastolic dysfunction and natriuretic peptides, subjects were classified in four groups: control group (no diastolic dysfunction/normal natriuretic peptides, 57%), no diastolic dysfunction/high natriuretic peptides (9%), diastolic dysfunction/normal natriuretic peptides (24%), and diastolic dysfunction/high natriuretic peptides (11%). We applied Cox multivariable and Classification and Regression Tree analyses. The mean age of the population was 69 ± 7 years, 44% were women, mean left ventricular ejection fraction was 61%, and 35% had diastolic dysfunction. During a median follow-up of 5.7 years, 95 heart failure/death events occurred. Overall, diastolic dysfunction and natriuretic peptides were predictive of adverse events (respectively, hazard ratio 1.91, confidence interval 1.19-3.05, = 0.007, and hazard ratio 2.25, confidence interval 1.35-3.74, = 0.002) with Cox analysis. However, considering the four study subgroups, only the group with diastolic dysfunction/high natriuretic peptides had a significantly worse prognosis compared to the control group (hazard ratio 4.48, confidence interval 2.31-8.70, < 0.001). At Classification and Regression Tree analysis, diastolic dysfunction/high natriuretic peptides was the strongest prognostic factor (risk range 24-58%). The DAVID-Berg data suggest that we look for the quite common combination of diastolic dysfunction/high natriuretic peptides to correctly identify asymptomatic subjects at greater risk for incident heart failure/death, thus more suitable for preventive interventions.